A secure approach for health information exchange using mobile personal health records / Mohamed Shabbir Hamza Abdulnabi - Mohamed Shabbir Hamza , Abdulnabi (2018)
Sharing patient information between different care providers has been identified early as a key enabler for quality and cost-effective healthcare. Being in the information age, it seems natural to expect immediate access to health information in the right place at the right time and in a usable format. However, the realization of such vision is taking too long, and the level of providers’ engagement is witnessing a decline. Difficulties in ensuring global connectivity, interoperability and concerns on security have always hampered attempts by the governments to deploy nationwide Health Information Exchange (HIE) successfully. An important question to pose is how new approaches can address the same issues of interoperability and interconnectivity without disturbing existing infrastructure and imposing much costs. Bearing in mind the pervasiveness and power of modern smartphones, this thesis proposes an alternative approach for nationwide HIE that can replace or complement governmental efforts, such as the Malaysian MyHIX project. The main objective is to introduce the idea of a multicomponent and distributed solution for large-scale HIE as a novel approach that differs from the existing central approaches but does not disturb the current set-up and attribute no significant costs to any of the involved stakeholders. The proposed approach provides a distributed framework in which patient data are carried by the patients themselves in the form of mobile Personal Health Records (mPHRs), typically on their handheld smartphones. This method uses the concept of mPHR in a novel way –as distributed storage units– and is to be compared with the current central approaches that aim to collect patient data in central repositories and circulate them via central engines. The individual mPHR systems are capable of interconnecting securely with multiple healthcare systems through a suitable interface. This interface is another app that runs on a special terminal device (such as a tablet) at the end of the healthcare system to ensure the interoperability with the patients’ smartphones. The detailed design and operation of the proposed approach is provided and justified, resulting in a multicomponent and coherent framework for HIE. The proposed framework consists of three main components: an mPHR at the side of the patient, legacy Health Information System (HIS) at the side of healthcare providers, and an interface device between the two. The whole framework is validated through a prototype implementation using software apps for the mPHR and the interface layer, and open source Electronic Medical Record (EMR) systems to represent legacy HISs used by healthcare providers. Various simulated use cases and scenarios have been presented to show the operation of the framework and its overall validity. Endorsement of the proposed framework can lead to a practical solution to the hard problem of HIE that avoids the cost of implementing a single global network to connect all healthcare systems, and ensures that the required data of each patient is available whenever and wherever it is needed.